2017
DOI: 10.4236/acs.2017.71001
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Combustible Gases at Traffic and Practising Waste Dumpsite in Freetown, Sierra Leone: A Pilot Study

Abstract: An assessment of the emission of combustible gases in developing countries requires reliable analytical realtime monitors that can rapidly screen them with minimal handling. Considering the expensive nature of monitoring environmental pollutants, chemical sensors are expected to play a pivotal role in measuring and recording environmental data. The Drager X am 5000 was used to report emission levels of combustible gases in this study, namely; nitrogen dioxide (NO 2 ), sulphur dioxide (SO 2 ) and carbon monoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The findings in our study are in agreement with those reported previously. 53 It was observed that anthropogenic activities contributed to more PAH pollutants at KT, followed by WL. These activities could be potentially harmful to living organisms and the ecosystem to a certain extent since they are PAH generators.…”
Section: Resultsmentioning
confidence: 97%
“…The findings in our study are in agreement with those reported previously. 53 It was observed that anthropogenic activities contributed to more PAH pollutants at KT, followed by WL. These activities could be potentially harmful to living organisms and the ecosystem to a certain extent since they are PAH generators.…”
Section: Resultsmentioning
confidence: 97%
“…Another aspect of air pollution is Suspended Particulate Matter (SPM). Air pollution is largely linked to high rates of distress and mortalities resulting from respiratory and cardiovascular ailments [8 -11], with the emission of some basic pollutant gases (NOX, SOX and CO) from most municipalities indicated as major contributors [11].…”
Section: It Was Reported By the International Panel Onmentioning
confidence: 99%